2006
DOI: 10.1590/s0100-879x2006001100007
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and intracellular localization of insulin-like proteins from leaves of Bauhinia variegata

Abstract: Evidence based on immunological cross-reactivity and anti-diabetic properties has suggested the presence of insulin-like peptides in plants. The objective of the present study was to investigate the presence of insulin-like proteins in the leaves of Bauhinia variegata ("pata-de-vaca", "mororó"), a plant widely utilized in popular medicine as an anti-diabetic agent. We show that an insulin-like protein was present in the leaves of this plant. A chloroplast protein with a molecular mass similar to that of bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 35 publications
(31 reference statements)
7
35
0
7
Order By: Relevance
“…Bauhenina varigata alcoholic extracts have compounds with a retention times very close to that of soluble insulin, which means that both plant alcoholic extract have compound with chemical structure similarities to that of soluble insulin, excluding any factors affecting the retention time since all the compound were analyzed under the same chromatographic condition. ).this is in agreement with (19) which indicated that HPLC chromatographic analysis of Bauhinia varigata show insulin like properties. for Bauhenina varigata alcoholic extract, no deaths or toxicity signs and symptoms observed after 24h and 48 h in all concentration that was administered and therefore the LD50 is considered higher than 4000mg/kg (which is the crude or highest extract concentration) and according to (Loomis and Hayes, 1996) its considered slightly toxic.…”
Section: Discussionsupporting
confidence: 92%
“…Bauhenina varigata alcoholic extracts have compounds with a retention times very close to that of soluble insulin, which means that both plant alcoholic extract have compound with chemical structure similarities to that of soluble insulin, excluding any factors affecting the retention time since all the compound were analyzed under the same chromatographic condition. ).this is in agreement with (19) which indicated that HPLC chromatographic analysis of Bauhinia varigata show insulin like properties. for Bauhenina varigata alcoholic extract, no deaths or toxicity signs and symptoms observed after 24h and 48 h in all concentration that was administered and therefore the LD50 is considered higher than 4000mg/kg (which is the crude or highest extract concentration) and according to (Loomis and Hayes, 1996) its considered slightly toxic.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of the active compounds such as flavonoids that found in B. variegata leaves on glucose levels in the serum of diabetic mice caused a significant decrease in blood glucose levels in diabetic mice similar to that reported on the hypoglycemic activity of Bauhinia variegate in diabetic patients by Azevedo et al, [20]. Several published study showed that streptozotocin-diabetic rats treated with a decoction of Bauhinia forficata leaves presented a significant reduction in serum and urinary glucose as compared to streptozotocindiabetic controls [21].…”
Section: -2 Hplc Analysissupporting
confidence: 83%
“…We detected a protein band in the same position as a bovine insulin band with a molecular mass of approximately 6 kDa. Experimental insulin showed an identical electrophoretic mobility with human insulin (5.8 kDa), bovine insulin (5.7 kDa) and other plant insulins from Momordica charantia (11 kDa; Khanna et al 1976), Spinacea oleracea and L. gibba (6 kDa; Collier et al 1987), Vigna unguiculata (6 kDa; Venâncio et al 2003) and Bauhinia variegate (5.7 kDa; Azevedo et al 2000). During Western blotting, SDS-PAGE gels were treated with the anti-insulin antibody and the band observed at the same position as bovine insulin.…”
Section: Discussionmentioning
confidence: 82%